An entrepreneurial framework for deciding on the implementation of large format digital printing internationally - Adendorff, Christian Michael (Rhodes University, Faculty of Commerce, Department of Management, 2003)
This study focuses on entrepreneurs within the SME sector using large format digital printing (LFDP) because of the changes in technology that influences the decisionmaking processes of the entrepreneur in the purchasing of a new LFDP. These fast changes are likely to continue and can cause technologies to become obsolete overnight. The entrepreneurs within the LFDP industry find themselves in the midst of these fast changes and are faced with a dilemma. On the one hand, they need to make sure that the technology used produces consistent and quality products. On the other hand, the entrepreneur needs to ensure an optimal return on investments. From the literature and the findings of the study, the researcher recommends a change to an existing model on a consultant involvement purchase of high technology products, which is then adapted to integrate resource-forecasting areas together with timing and type of information required as well as external environment scanning. The existing model's focus is on the individual's ability to make decisions based on their own knowledge. However, by integrating technology forecasting components, and scanning the business environment and resource forecasting needed the decision-maker will be better equipped to make decisions that also takes into account the external environment. This will also allow them to plan and manage growth in a systematic way. Therefore the proposed model takes into account individual capabilities and technology forecasting components that can facilitate the decision-making process. The adapted model on decision-making clearly delineates that the combination of entrepreneurial qualities and technology forecasting techniques in the LFDP industry will ultimately assist the entrepreneur on various levels in deciding on a new LFDP.
Keywords: Entrepreneurship; Success in business; Business -- Technological innovations; Digital printing